COVID-19: Are We Ready for the Second Wave? - Ali, Inayat (Disaster Med Public Health Prep, 2020)
The coronavirus disease 2019 (COVID-19) pandemic has already exerted an enormous impact on the entire world. Everything is overwhelmed in the face of a rapid escalation of cases. The countries that have already reported the peak of transmission are easing their preventive measures yet fearing a second wave of infection. If the virus causes that next wave, are we sufficiently prepared to deal with it? I argue that the stakeholders concerned should simultaneously handle the ongoing pandemic while making effective preparations for its second wave. To relax the preventive measures, countries must thoroughly revisit their situations based on scientific evidence.